MicroRNA-3614 regulates inflammatory response via targeting TRAF6-mediated MAPKs and NF-κB signaling in the epicardial adipose tissue with coronary artery disease. (1st February 2021) - Huang, Wenhua; Wu, Xinggang; Xue, Yajun; Zhou, Yijun; Xiang, Hui; Yang, Wenkai; Wei, Yutao
Abstract: Objective: The inflammatory status of epicardial adipose tissue (EAT) is one of the factors leading to the development of related diseases such as coronary artery disease (CAD). The thickness of CAD EAT increases and is accompanied with increased macrophage infiltration and heightened inflammatory responses. However, microRNAs (miRNAs) regulating the inflammatory responses of macrophages in CAD EAT remain unclear. Method: miRNA expression profiles of CAD EATs and non-CAD EATs were determined by miRNA microarrays. Quantitative real-time reverse transcription-polymerase chain reaction, Western blotting, immunohistochemical assay, and fluorescence in-situ hybridization were adopted to detect miR-3614 expression and function in EATs and macrophages. The interaction between miR-3614 and tumor necrosis factor receptor-associated factor 6 (TRAF6) was identified using an online website combined with a dual-luciferase reporter assay. Enzyme-linked immunosorbent assay was performed to detect the expression of inflammatory cytokines. Results: The decreased expression of miR-3614 was identified in CAD EAT. The level of miR-3614 was down-regulated by lipopolysaccharide (LPS) in macrophages, whereas LPS-induced inflammatory injury can be reduced by miR-3614 overexpression. TRAF6 was predicted and verified to be a target of miR-3614. The phosphorylated levels of kinases in the mitogen-activated protein kinase (MAPK) and nuclear factor (NF)-κB pathways were inhibited by miR-3614 overexpression. Importantly, the knockdown of TRAF6 inhibited the LPS-induced inflammatory cytokine expressions in cells. Conclusion: A novel negative feedback loop by miR-3614 possibly contribute to the regulation of inflammatory processes via targeting the TRAF6/MAPK/NF-κB pathway in EATs and prevents an overwhelming inflammatory response. Highlights: miR-3614 is down-expressed in epicardial adipose tissue (EAT) with coronary artery disease (CAD). Studies with cultured macrophages suggest that miR-3614 can be stimulated by toll-like receptor activators. miR-3614 targeted TRAF6 to repress the MAPKs/NF-κB pathway in macrophages. miR-3614 suppress inflammatory response through MAPKs/NF-κB pathway in CAD EAT, which decreases expression of the TRAF6.